The Impact of Digital Culture in the Curriculum 2013 Report Card Processing Process in Elementary Schools - Sriwati, Sriwati (Jurnal Pendidikan Indonesia, 2022)
SDN Sukaasih 1 is one of the elementary schools in the Pasarkemis sub-district, Tangerang Regency, which has applied the Curriculum 2013 learning. The data processing uses the K13 report card application based on Microsoft Excel. The purpose of this study was to determine the impact of digital culture in the process of processing Curriculum 2013 (K13) report cards at SDN Sukaasih 1. The method used in this research is a descriptive method with a qualitative approach. Techniques of collecting data through observation, interviews, and documentation studies. The number of informants in the research was one person who was a teacher and homeroom teacher at SDN Sukaasih 1. The results showed that the impact of digital culture in the processing of K13 report cards, namely, teachers were encouraged or motivated to understand science and technology better; Increasing the quality of human resources through the development and use of information and communication technology; Utilizing K13 Report Card Processing can make it easier for teachers/homeroom teachers to make student report cards; Administrative grades are tidier, more organized in 1 folder, which is usually handwritten in several book notes. The growth of innovation in various fields that are oriented towards digital technology which facilitates the process of work